1970
DOI: 10.1055/s-0038-1654230
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin- und Antiplasminwirkung von 4-Amidinophenylbrenztraubensäure (APPA) in vivo

Abstract: ZusammenfassungEs wurde die Antithrombin- und Antiplasmin Wirkung der 4-Amidinophenylbrenztraubensäure (APPA) an Kaninchen untersucht. Dabei hat sich gezeigt, daß die in biochemischen Untersuchungen als kompetitiver Hemmstoff der Gerinnungsfermente wirkende Verbindung auch in vivo antikoagulierende und antifibrinolytische Wirkungen entfaltet, die sich sowohl nach intravenöser als auch nach oraler Gabe des Inhibitors messend verfolgen lassen.Die Wirkung von Thrombininfusionen oder Streptokinaseinfusionen wurde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…So far three other enzymes in the blood may be properly described as serine proteinases: plasmin, serum kalli-krein and C I'-esterase. Investigations on the influence of synthetic inhibitors on these enzymes have shown that they also can be inhibited in a different degree [3,44,47,48,56], In this connection it is noteworthy that with some benzamidine derivatives the ability to inhibit these enzymes is much less pronounced than with others. This observation should encourage attempts to obtain separate inhibitors for each of the serine proteinases of the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far three other enzymes in the blood may be properly described as serine proteinases: plasmin, serum kalli-krein and C I'-esterase. Investigations on the influence of synthetic inhibitors on these enzymes have shown that they also can be inhibited in a different degree [3,44,47,48,56], In this connection it is noteworthy that with some benzamidine derivatives the ability to inhibit these enzymes is much less pronounced than with others. This observation should encourage attempts to obtain separate inhibitors for each of the serine proteinases of the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the pharmacodynamics and pharmacokinetics of the most effective inhibitors had shown that APPA is a suitable tool for studying the antithrombin effect of such inhibitors in vivo [47]. Already at this time, this inhibitor can serve as a usefull pharmacological model for compounds of this nature and allows an estimate for the potential therapeutic effect of this class of drugs.…”
Section: Pharmacological Aspects O F Synthetic Inhibitorsmentioning
confidence: 99%
“…A lowered plasminogen level found in the presence of increased dose of DV 1006 might be dne to an effect of DV 1006 added which was not completely removed from the eugloublin precipitate by washing. Markwardt et al 1970). These inhibitors chemically belong to amidino and guanidino compounds.…”
Section: Inhibition Of Caseinolytic Activity Induced By Sk-plasminogenmentioning
confidence: 99%
“…Recently several investigators have reproted the similar activities of synthetic amidino and guanidino compounds (Muramatsu and Fujii 1968, Geratz 1970, Markwardt et al 1970.…”
mentioning
confidence: 99%
“…Benzamidine is known to inhibit several serine proteases like plasma kallikrein (Yano et al 1970;Markwardt et al 1971a & b;Asghar et a!. 1976)and plasminogen activators (Geratz 1970;Markwardt et al 1970;Landmann 1973). Plasma kallikrein could hardly be responsible for the loss of HMrK cofactor capacity in the absence of benzamidine.…”
mentioning
confidence: 99%